POLA KONSUMSI DAN PERMINTAAN PANGAN POKOK BERDASARKAN ANALISIS DATA SUSENAS 2005 - Anna Vipta Resti Mauludyani; Drajat Martianto; Yayuk Farida Baliwati (Jurnal Gizi dan Pangan, 2008)
Food demand can be found dynamic, altering by the change in price and income. How great the influence of those changes to food consumption is the important information as the basic consideration for government in creating policy related to food consumption. The objective of the research, which has survey design, was to analyze staple food consumption and demand pattern in household in Indonesia. The research was conducted in Bogor, from March to June 2008 by using secondary data Susenas year 2005 with 64.709 households as the samples. The staple food analyzed were rice, corn, cassava, sweet potato, wheat flour and its derived product (instant noodle, noodle). Data was processed by SAS program version 6.12 and Double-Log Regression econometrical model. Then, it was analyzed descriptively. Result shows that rice has the biggest expenditure proportion among staple food. Almost all staple food is obtained by purchasing, except in corn, cassava, and sweet potatoes. Energy contribution from rice reaches half of total energy consumption. The consumption of rice, corn, cassava, sweet potatoes, wheat flour and its derived product, instant noodle, and wheat noodle per capita per year are 100.52 kg, 3.36 kg, 11.67 kg, 4.10 kg, 5.09 kg, 3.39 kg, and 0.22 kg. Staple food which has consumption participation level almost 100% is rice. The own price elasticity of staple foods are not elastic, except in corn, wheat flour and its derived product. The income elasticity of all staple foods is not elastic in all category of region and income stratification. The demand elasticity of staple food give some implications on consumption and food consumption improvement, they are: 1) raising price of staple food can decrease consumption, thus, price stability is very important, 2) almost all staple foods has not elastic income elasticity, so that food consumption improvement needs great stimulus of increasing income, 3) poor household is greatly influenced by the increasing of price, thus, food consumption improvement for them must be conducted by doing many relevant efforts, 4) target of decreasing rice consumption is still cannot be reached, so that staple food diversification must be continuously developed, 5) in order to develop local food consumption, like corn, cassava, and sweet potato, the development of agro industry based on local food and Communication Information Education (CIE) about food consumption diversification are essential to be conducted.